Strategi Komunikasi Pemasaran Desa Wisata Dalam Meningkatkan Kunjungan Wisatawan Pasca Pandemi Covid-19: - Annisa, Arhetta Putri (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
The presence of the Covid 19 pandemic and government policies have had a major impact on the industrial and business world, one of which is in the tourism sector. Tourism is one of the sectors affected by the COVID-19 pandemic. This research is based on the decrease in the number of tourist visits to the Jambu Tourism Village due to the Covid-19 pandemic until now where the number of tourist visits has begun to increase. The purpose of this research is to find out the marketing communication strategies carried out by the management of the Jambu Tourism Village to increase the number of tourist visits after the Covid-19 pandemic. The method used in this research is descriptive qualitative. This study uses the theory of AISAS analysis. Based on the research conducted, the management of the Jambu Tourism Village conducted Social Media Marketing (SMM), in collaboration with the Kediri Regency Tourism Office, and utilized point Search and Share on AISAS Theory which was also supported by the power of word of mouth.